2018
DOI: 10.21873/invivo.11286
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 27 Expression in EUS-FNA Samples Can Predict Gemcitabine Sensitivity in Pancreatic Cancer

Abstract: Abstract. Background/Aim: Gemcitabine (GEM) Pancreatic cancer shows one of the worst prognoses among all malignant tumors since it progresses quickly and is difficult to diagnose at an early stage. Advances in chemotherapy are considered to be important for improving the prognosis of unresectable cases.Burris et al.(1) reported that gemcitabine (GEM) can significantly prolong survival in comparison to 5-FU for unresectable pancreatic cancer. Recently, FOLFIRINOX (L-OHP, CPT-11, 5-FU, LV) therapy (2) and GEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In addition, our report reinforces the critical role of the p38MAPK signalling pathway in the cellular response to gemcitabine in agreement with previous data showing that p38α mediates the apoptotic response to this drug [17,34]. In fact, downstream targets of p38MAPK, as MAPKAPK2 or HSP27, have been related to a resistant phenotype [35][36][37][38] and also considered as putative biomarkers [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our report reinforces the critical role of the p38MAPK signalling pathway in the cellular response to gemcitabine in agreement with previous data showing that p38α mediates the apoptotic response to this drug [17,34]. In fact, downstream targets of p38MAPK, as MAPKAPK2 or HSP27, have been related to a resistant phenotype [35][36][37][38] and also considered as putative biomarkers [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…[ 74 ] Levels of hENT1 and HSP27 in FNA tissue also seem to predict sensitivity to gemcitabine in patients with unresectable pancreatic cancer. [ 75 76 ] Only a few studies addressed the question whether FNA or FNB is superior in terms of sample adequacy for next-generation sequencing (NGS). Larson et al observed no difference between the two needle types,[ 77 ] but in a larger trial by Elhanafi et al including 167 patients, the proportion of samples sufficient for NGS was higher in the FNB group.…”
Section: Novel Applications and Future Aspectsmentioning
confidence: 99%
“…Expression of HSP72 on EUS-FNA samples, evaluated through IHC, was significantly associated with that on resected specimens and was a helpful predictive marker for sensitivity to gemcitabine (GEM). GEM-resistance rate was significantly higher in patients with overexpression of p-HSP27, and the survival rate was significantly lower if p-HSP27 (Ser82) detection rate was > 51.6%[45]. Another important molecular biomarker for prediction of GEM sensitivity in unresectable PDAC was S100A4 mRNA expression, analyzed in EUS-FNA samples through qRT-PCR analysis.…”
Section: Feasibility and Clinical Utility Of Pancreatic Endoscopic Ulmentioning
confidence: 99%